2007
DOI: 10.2133/dmpk.22.267
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Angiotensin Receptor Blockers on CYP2C9 Activity in Human Liver Microsomes

Abstract: We investigated the inhibitory effects of the angiotensin receptor blockers (ARBs), candesartan, irbesartan, losartan, losartan active metabolite (EXP-3174), olmesartan, telmisartan and valsartan (0.3-300 microM), on the CYP2C9 activity in human liver microsomes using (S)-(-)-warfarin as a typical CYP2C9 substrate. Except for olmesartan and valsartan, these ARBs inhibited the activity of 7-hydroxylation of (S)-(-)-warfarin with IC50 values of 39.5-116 microM. Of six synthetic derivatives of olmesartan, five co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Olmesartan, which has a lower affinity for CYP2C9, 25) showed intermediate inhibition of CYP2C8 in the present study. Candesartan has been reported to have weak effects on the inhibition of CYP2C8, and to have negligible accumulation with rapid elimination of radioactivity in plasma after administration of 14 C-labeled drugs.…”
Section: Discussionsupporting
confidence: 40%
“…Olmesartan, which has a lower affinity for CYP2C9, 25) showed intermediate inhibition of CYP2C8 in the present study. Candesartan has been reported to have weak effects on the inhibition of CYP2C8, and to have negligible accumulation with rapid elimination of radioactivity in plasma after administration of 14 C-labeled drugs.…”
Section: Discussionsupporting
confidence: 40%
“…20) Using this method, we demonstrated that several ARBs inhibit AA metabolism in recombinant CYP (rCYP) 2C8, 21) rCYP2C9, rCYP2J2, and HLMs 22) ; among the ARBs, telmisartan exhibited more potent inhibitory effect towards the CYP enzymes. 21,22) Several studies have revealed that telmisartan inhibits CYP2C9 23) and CYP2J2 24) in HLMs. Ren et al 24) reported that telmisartan is a mixed inhibitor of CYP2J2.…”
mentioning
confidence: 99%
“…It is possible to assess the transport activity via these efflux transporters using Caco-2 cells cultured for 1 week as a first tier screening assay. However, it is difficult to correctly assess the transcellular transport activity of high hydrophilic compounds in Caco-2 cells cultured for 1 week, because the transcellular transport activity of olmesartan, a good substrate for hMRP2 (Nakagomi-Hagihara et al, 2006) and also a hydrophilic compound (Kamiyama et al, 2007), was observed only in the 2-week culture. Therefore, we suggest that it is better to perform a transport study as a first tier screening assay using Caco-2 cells cultured for 2 weeks rather than 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, four test compounds were selected: 1) digoxin, a typical hMDR1 substrate (Pedersen et al, 1983); 2) ochratoxin A, a specific substrate for hMRP2 that showed transcellular transport activity across Caco-2 cells (Berger et al, 2003); 3) olmesartan, a highly hydrophilic substrate for hMRP2 (Nakagomi-Hagihara et al, 2006;Kamiyama et al, 2007); and 4) estrone-3-sulfate (ES), a typical substrate of hBCRP (Xia et al, 2005).…”
mentioning
confidence: 99%